Cold mountain : a novel - Frazier, Charles, 1950- (New York : Vintage Books, 1998)
Inman, an injured and disillusioned Confederate soldier, embarks on a harrowing journey home to his sweetheart, Ada, who herself is struggling to run the farm left her at her father's sudden death.
Keywords: United States -- History -- Civil War, 1861-1865 -- Fiction; Love stories; Love stories; Historical fiction; Adventure fiction